2021
DOI: 10.3390/s21186181
|View full text |Cite
|
Sign up to set email alerts
|

Particle Classification through the Analysis of the Forward Scattered Signal in Optical Tweezers

Abstract: The ability to select, isolate, and manipulate micron-sized particles or small clusters has made optical tweezers one of the emergent tools for modern biotechnology. In conventional setups, the classification of the trapped specimen is usually achieved through the acquired image, the scattered signal, or additional information such as Raman spectroscopy. In this work, we propose a solution that uses the temporal data signal from the scattering process of the trapping laser, acquired with a quadrant photodetect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
(60 reference statements)
0
8
0
Order By: Relevance
“…For this, the forward scattered signal of the trapping beam is collimated with a 10x condenser lens before being steered into a quadrant photodetector (PDQ80A-Thorlabs), using a relay lens to image the back focal plane of the condenser. In specific, for each particle, we obtain a set of three signals (X, Y, and SUM, see figure 1(C)) which can be related to the positions of the particle upon calibration [5]. Nevertheless, even without the calibration factor, the signals already contain information that relates to the physical properties of each individual particle as discussed before, namely size and refractive index.…”
Section: Particle Classificationmentioning
confidence: 99%
See 2 more Smart Citations
“…For this, the forward scattered signal of the trapping beam is collimated with a 10x condenser lens before being steered into a quadrant photodetector (PDQ80A-Thorlabs), using a relay lens to image the back focal plane of the condenser. In specific, for each particle, we obtain a set of three signals (X, Y, and SUM, see figure 1(C)) which can be related to the positions of the particle upon calibration [5]. Nevertheless, even without the calibration factor, the signals already contain information that relates to the physical properties of each individual particle as discussed before, namely size and refractive index.…”
Section: Particle Classificationmentioning
confidence: 99%
“…OT systems can also be adapted for indirect monitoring of physical and chemical processes. One such method involves studying the scattered radiation from the optically trapped specimen [4], which has motivated the development of identification and classification tools based on optical trapping [4,5]. On the other hand, these setups have also been combined with different probing techniques for a more comprehensive study of the trapped particles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Being sensitive to the displacement of the trapped particle in the transverse directions, the acquired signal from the quadrant photodetector allows to probe the Brownian motion of the trapped beads which contains information regarding the physical properties of the particle [1]. In the recent years, our team explored a few strategies for single particle/cell classification using optical trapping systems and scattered radiation, both using the back-scattered [2] and forward scattered signal [3]. Focusing on the latter for the purpose of this work, we reported the classification of trapped particles by introducing an algorithm that consists on performing a dimensional reduction with Principal Component Analysis performed in the Fourier space before the application of common classification strategies such as K-nearest neighbors.…”
Section: Classification Of Particles Using Pca Decompositionmentioning
confidence: 99%
“…Furthermore, when integrated with a quadrant-photodetector, see figure 1, OT can also probe the dynamical properties of a trapped particle by tracking the position using the forward scattered light. Recently, it has been shown that these dynamics can be used to identify and classify particles through a careful analysis of the position timeseries and machine learning algorithms, which can be fundamental for future integration into intelligent microfluidic devices [3].…”
Section: Introductionmentioning
confidence: 99%